Entrepreneurial ventures and the developmental state: Lessons from the advanced economies - William Lazonick (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
A basic intellectual challenge for those concerned with the poverty of nations is to come to grips with the nature and causes of the wealth of the world's wealthier nations. One might then be in a position to inform the poorer nations how they might achieve similar outcomes. This paper is organized around what I call the theory of innovative enterprise, a perspective derived from the historical and comparative study of the development of the advanced economies. The theory of innovative enterprise provides the essential analytical link between entrepreneurship and development. Section 2 offers, as a point of departure, a contrast between entrepreneurship in rich and poor nations. Section 3 outlines the theory of the innovating firm in which entrepreneurship has a role to play. Section 4 identifies the roles of entrepreneurship in new firm formation in terms of the types of strategy, organization, and finance that innovation requires, and emphasizes the disappearance of entrepreneurship with the growth of the firm. In Section 5 I argue that, in the advanced economies, successful entrepreneurship in knowledge intensive industries has depended heavily upon a combination of business allocation of resources to innovative investment strategies, and government investment in the knowledge base, state sponsored protection of markets and intellectual property rights, and state subsidies to support these business strategies. One cannot understand national economic development without understanding the role of the developmental state. At the same time, the specific agenda and ultimate success of the developmental state cannot be understood in abstraction from the dynamics of innovative enterprise. It is through the interaction of the innovative enterprise and the developmental state that entrepreneurial activity inserts itself into the economic system to contribute to the process of economic development.
Keywords: L2; O1; O3; P1; 330; entrepreneurship; innovative enterprise; developmental state